The Organization of Islamic Educational Institutions - Riyo Arie Pratama; Heri Okta Pratama; Sri Wulandari; Intan Gustiana; Andri Saputra; Nurul Hidayati Murtafiah (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2024)
The organization of Islamic educational institutions plays an important role in creating an effective education system that is in accordance with Islamic values. Islamic educational institutions, both at the formal and non-formal levels, require a clear organizational structure to achieve optimal educational goals. This article discusses various aspects of organizing Islamic educational institutions, including the role of leaders, human resource management, and curriculum management based on Islamic principles. This article also explains the importance of collaboration between various parties, such as teachers, parents, and the community, to create an educational environment that supports the development of character and intelligence of students. In addition, this study also discusses the challenges faced by Islamic educational institutions in facing developments in the era, such as technological changes and globalization. Good organization in Islamic educational institutions is expected to form individuals who are not only intellectually intelligent, but also strong in faith and morals. This study concludes that in order to achieve the ideal goals of Islamic education, Islamic educational institutions need to apply effective, flexible, and adaptive managerial principles to the dynamics of society.